Functional Complementation Analyses Reveal that the Single PRAT Family Protein of Trypanosoma brucei Is a Divergent Homolog of Tim17 in Saccharomyces cerevisiae - Weems, Ebony (Eukaryot Cell, 2015)
Trypanosoma brucei, a parasitic protozoan that causes African trypanosomiasis, possesses a single member of the presequence and amino acid transporter (PRAT) protein family, which is referred to as TbTim17. In contrast, three homologous proteins, ScTim23, ScTim17, and ScTim22, are found in Saccharomyces cerevisiae and higher eukaryotes. Here, we show that TbTim17 cannot rescue Tim17, Tim23, or Tim22 mutants of S. cerevisiae. We expressed S. cerevisiae Tim23, Tim17, and Tim22 in T. brucei. These heterologous proteins were properly imported into mitochondria in the parasite. Further analysis revealed that although ScTim23 and ScTim17 were integrated into the mitochondrial inner membrane and assembled into a protein complex similar in size to TbTim17, only ScTim17 was stably associated with TbTim17. In contrast, ScTim22 existed as a protease-sensitive soluble protein in the T. brucei mitochondrion. In addition, the growth defect caused by TbTim17 knockdown in T. brucei was partially restored by the expression of ScTim17 but not by the expression of either ScTim23 or ScTim22, whereas the expression of TbTim17 fully complemented the growth defect caused by TbTim17 knockdown, as anticipated. Similar to the findings for cell growth, the defect in the import of mitochondrial proteins due to depletion of TbTim17 was in part restored by the expression of ScTim17 but was not complemented by the expression of either ScTim23 or ScTim22. Together, these results suggest that TbTim17 is divergent compared to ScTim23 but that its function is closer to that of ScTim17. In addition, ScTim22 could not be sorted properly in the T. brucei mitochondrion and thus failed to complement the function of TbTim17.